2022
DOI: 10.3390/su14095578
|View full text |Cite
|
Sign up to set email alerts
|

Female Corporate Leadership and Firm Growth Strategy: A Global Perspective

Abstract: This study aims to understand the relationship between female corporate leadership and firm performance based on exploration and exploitation strategies using a global enterprise data set. Previous studies report conflicting evidence of female corporate leadership on firm performance. This study applies an exploration–exploitation framework and suggests that the relative advantage of female corporate leadership relies upon certain aspects of the firm’s growth strategy. The empirical evidence confirms that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…This social construct has influenced how females and males should react to their leader’s mistreatment. Evidence suggested that subordinates’ gender significantly influenced responses to their leaders (Daraba et al , 2021; Ouyang et al , 2015), whereas leaders’ gender showed no significant effects on how they treat subordinates (Collins et al , 2014; Eagly et al , 2003; Laidoja et al , 2022).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…This social construct has influenced how females and males should react to their leader’s mistreatment. Evidence suggested that subordinates’ gender significantly influenced responses to their leaders (Daraba et al , 2021; Ouyang et al , 2015), whereas leaders’ gender showed no significant effects on how they treat subordinates (Collins et al , 2014; Eagly et al , 2003; Laidoja et al , 2022).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Empirical research on how CEO gender (i.e., female or male) relates to firm performance is equivocal, with available evidence not allowing a clear conclusion (Laidoja, Li, Liu, & Ren, 2022). Indeed, most studies find no systematic relationship between the gender of the CEO and firm performance (for recent examples, (Al-Begali & Phua, 2023;Brush & Elam, 2023;Espinosa-Méndez & Correa, 2022;Kubo & Nguyen, 2021)), and those that find are inconsistent in their results, some identifying male (Wang, Holmes Jr, Devine, & Bishoff, 2018) and some female CEOs (e.g., (Hoang, Nguyen, & Van Tran, 2019)) connected with firm financial performance.…”
Section: Introductionmentioning
confidence: 99%
“…Women's engagement in small businesses may significantly impact many African countries' economic growth. Even in women-friendly countries or regions, females outnumber males as small business owners or operators (Laidoja, Li, Liu, & Ren, 2022). Although women contribute to the economy as business owners and entrepreneurs, gender is ignored in impoverished economies (Alon, Doepke, Olmstead-Rumsey, & Tertilt, 2020;Alsos, Isaksen, Ljunggren, 2006;Waring, 1988).…”
Section: Introductionmentioning
confidence: 99%